Pengaruh Pijat Akupresur Laktasi (Akuprelaktasi) terhadap Produksi ASI pada Ibu Nifas di Kabupaten Tegal - Rahmanindar, Nora; Nisa, Juhrotun (LPPM Hang Tuah Pekanbaru, 2024)
In Tegal Regency in 2022, the coverage of babies aged under 6 months who receive exclusive breastfeeding is 67.96%. Tegal Regency Government is currently continuing to strive for 2026 coverage of babies aged under 6 months who receive exclusive breast milk of 85%. This research aims to determine the effect of lactation acupressure massage on breast milk production in postpartum mothers. Quantitative research uses a quasi-experimental design with a non-equivalent control group design. The population in this study was postpartum mothers in the Tegal Regency, namely 100 postpartum mothers. The sampling period was from November until December 2023; the samples used were all postpartum mothers on days 1-3. The sampling technique used a cluster sampling technique; 50 postpartum mothers were in the treatment group, and 50 postpartum mothers were in the control group. The results of statistical tests using Wilcoxon obtained a P-value of 0.000 at a significance level of 5% (0.000<0.005), in this case indicating that the research hypothesis was accepted, meaning that there was an effect of lactation acupressure massage on breast milk production in postpartum mothers.